2021
DOI: 10.5194/hess-25-4585-2021
|View full text |Cite
|
Sign up to set email alerts
|

Simulated or measured soil moisture: which one is adding more value to regional landslide early warning?

Abstract: Abstract. The inclusion of soil wetness information in empirical landslide prediction models was shown to improve the forecast goodness of regional landslide early warning systems (LEWSs). However, it is still unclear which source of information – numerical models or in situ measurements – is of higher value for this purpose. In this study, soil moisture dynamics at 133 grassland sites in Switzerland were simulated for the period of 1981 to 2019, using a physically based 1D soil moisture transfer model. A comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 88 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…To this end, the temporal saturation variation was simulated using the coupled heat and mass transfer model CoupModel (Jansson and Karlberg, 2011), and the same model set-up, input data, and parametrization were used at both sites. We used the same model set-up as in Wicki et al (2021), and we refer to this study for a detailed model description. To account for the different topographic and hydrogeological settings, the lower model boundary conditions were adjusted by explicitly including the elevation difference and horizontal distance to the nearest drainage point.…”
Section: Agreement Of Soil Wetness Measurements With Prevalent Model ...mentioning
confidence: 99%
“…To this end, the temporal saturation variation was simulated using the coupled heat and mass transfer model CoupModel (Jansson and Karlberg, 2011), and the same model set-up, input data, and parametrization were used at both sites. We used the same model set-up as in Wicki et al (2021), and we refer to this study for a detailed model description. To account for the different topographic and hydrogeological settings, the lower model boundary conditions were adjusted by explicitly including the elevation difference and horizontal distance to the nearest drainage point.…”
Section: Agreement Of Soil Wetness Measurements With Prevalent Model ...mentioning
confidence: 99%
“…Lastly, Wicki et al (2021) compared the reliability of landslides forecast models based on simulated soil moisture with respect to models based on soil moisture measurements. Specifically, they assessed the potential and limitations of adopting 1D soil water transfer model for regional LEWS and disclosed the pros and cons compared of using soil moisture measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they assessed the potential and limitations of adopting 1D soil water transfer model for regional LEWS and disclosed the pros and cons compared of using soil moisture measurements. To this aim, they used plot-scale soil hydrological simulations to be able to directly compare the results to a landslide forecast model based on in situ soil moisture measurements and demonstrated a high information content of simulated soil moisture for regional landslide activity, which was even higher than when in situ soil moisture measurements were used (Wicki et al, 2021). In this regard, Wicki et al (2020b), demonstrated that the performance is strongly dependent on the distance between the soil moisture network location and landslide activity area and that the goodness increases with decreasing distances between measurement sites and landslides.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of disaster risk is one of the most effective strategies to deal with various large-scale natural disasters. Landslide risk early warning represented by rainfall monitoring, soil water content and pore water pressure monitoring and deformation monitoring is widely used in engineering [12][13][14][15][16][17][18] . The main indicators to identify landslide risk include the abnormal increase of rainfall [19][20][21] , the increase of soil moisture content 13,[22][23][24][25][26][27] , the acceleration of slope deformation 28,29 .…”
mentioning
confidence: 99%